Pengaruh Modal Usaha terhadap Sikap Berwirausaha dan Peran Orang tua sebagai Variabel Moderating - Formaida Tambunan (Jurnal Maksipreneur, 2022)
This study aims to analyze venture capital's effect on entrepreneurial attitudes in Tanjung Rejo Village, Medan. This type of research is quantitative associative research. The population in this study is all entrepreneurs in the area of Tanjung Rejo Village, Medan. The sample using the Slovin formula obtained by 58 respondents with the sampling technique is simple random sampling. The data were obtained using a questionnaire by first testing the validity and reliability. The data were obtained using a questionnaire by first testing the validity and reliability. Data analysis used descriptive statistical analysis and Moderated Regression Analysis (MRA) with normality, multicollinearity, and heteroscedasticity tests first, then hypothesis testing was carried out. The results of the study found that business capital had an effect on entrepreneurial attitudes and the parental role moderated the impact of venture capital on entrepreneurial attitudes.